Climatology of hail in Argentina - Mezher, Romina N. (2012)
The annual cycle, annual and seasonal frequency and geographical distribution of hail in Argentina during the 1960-2008 period are examined. Eight regions covering the whole territory were defined based on the correlation of the mean annual hail frequency between all weather stations. Regions lying between 30° and 40°S as well as those dominated by mountains present the highest hail frequencies in Argentina. The eastern and coastal areas of the country experience hail events mainly during springtime but they may start in late winter and continue through the beginning of summer. Events in western and central Argentina also predominate in spring but the maximum frequencies are observed during summer months. Trends in the annual number of hail events calculated for each region indicate that events in northwestern and northeastern Argentina have been increasing as well as in southern Patagonia. On the other hand, in central Argentina, southern Buenos Aires-La Pampa, northern Buenos Aires-Litoral and northern Patagonia trends are negative and statistically significant in the first two regions, basically by the decrease of events during spring and summer.